Study on association between echocardiographic findings in COPD patients with severity of COPD (Mediscope, 2020)
Background: Patients with chronic obstructive pulmonary disease (COPD) are at increased risk of developing cardiovascular disease. Echocardiography (ECHO) carries information about cardiac diseases and prognosis in COPD patients.Objective: To find out the Echocardiography changes in COPD patients and to assess Right ventricular (RV) dysfunction by echocardiography and correlate with the disease severity.Methods: A prospective study was conducted on 70 patients admitted with symptoms and signs suggestive of COPD in the Department of Medicine, Gazi Medical College and Hospital (GMCH), Khulna from January 2017 to December 2018. Patients were diagnosed clinically as having COPD with confirmation by spirometry. The patients with asthma, bronchiectasis, tuberculosis, pneumoconiosis, restrictive lung disease like kyphoscoliosis, rheumatic, congenital, ischemic heart disease and hypertension were excluded from the present study.Results: Regarding symptoms, majority 65 (92.9%) patients had breathlessness, 58 (82.9%) had cough with sputum, 25 (35.7%) had swelling of feet. Regarding signs, 68 (97.1%) patients had tachypnea, 24 (34.3%) had raised JVP, 23 (32.9%) had loud P2 suggestive of pulmonary arterial hypertension. Regarding echocardiographic findings, 42 (60.0%) patients had Cor pulmonale, 32 (45.7%) had LVDD, 31 (44.3%) had RVH, 30 (42.9%) had PAH, 29 (41.4%) patients had RA/RV dilation, 11 (15.7%) had RVSD and 9 (12.9%) had LVH. Table 08 shows RA/RV dilatation, RVH, Cor pulmonale, PAH and LVDD were statistically significant (p